Identifying, analyzing, and prioritizing barriers in the Indian industrial and commercial rooftop solar sector. (April 2023) - Dhingra, Tarun; Sengar, Anita; Sajith, Shambhu
Highlights: To identifying and categorizing the barriers to the growth of roof top solar in India. To assess and prioritize these barriers. To deliver managerial and practical implications for these barriers. Market based barrier most critical barrier to roof top solar. Abstract: The adoption of rooftop solar in India is still relatively low, indicating substantial barriers. There is a lack of literature on comprehensively identifying various barriers to rooftop solar adoption. This research aims to fill the gap by creating a framework to identify and categorize the factors and sub-factors that stimulate the capacity of industrial and commercial rooftop solar in India. Thirty-five barriers were identified from an extensive literature review which is classified into five categories; Financial, Institutional & Regulatory, Location-based, Technical, and Market-based. Multi-criteria decision-making technique with a Fuzzy Analytical Hierarchy Process is used to prioritize these impediments. The analysis suggests that the most significant barriers materialized to thwart industrial and commercial rooftop solar growth in India are market-based and financial barriers. Institutional & Regulatory, Technical, and location-based barriers come next, respectively. This study is the first attempt to holistically inspect the barriers to identification, categorization, and prioritization of industrial and commercial rooftop solar in India. This investigation provides an important opportunity to advance the understanding of the significant barriers affecting the growth of industrial and commercial rooftop solar in India.